Coagulation Performance of a Novel Inorganic Polymeric Coagulant-Polyferric-Magnesium Sulfate - Wei, Yanxin; Ding, Aimin; Xu, Juncui; Bi, Jianhong (Asian Journal of Chemistry, 2011)
Coagulation processes are regarded as important environmental protection technology, finding wide applications in wastewater treatment facilities. The continuous need for more efficient coagulation processes have lead to the development of new modified coagulation reagents, such as polyferric magnesium sulphate (PFMS). The aim of the present study is to evaluate the coagulation performance of the reagents by treating a typical kaolin (clay) suspensions, printing and dyeing wastewater as well as wastewater from sauce plant, in comparison with the conventional polymer coagulants, i.e., polyaluminum chloride (PAC) and polyferric sulfate (PFS). The effect of coagulation efficiency, such as pH, the dosage of coagulant and the settling time were discussed. The results indicate that PFMS has the best coagulation efficiency under the optimum conditions (including pH at 6-9, the dosage of coagulant at 4.8 mg/L and the settling time at 20 min, respectively). Additionally, PFMS exhibits a better coagulation performance than the conventional polymer coagulants, i.e., polyaluminum chloride and polyferric sulfate in treatment of the wastewater.